Perbandingan Metode Identifikasi Usia Menggunakan Molar Ketiga antara Metode Demirjian Modifikkasi dengan Metode Harris and Nortje - Farhan Iskandar; Moch Atmaji Windrianto; Dharma Satya Aprianto; Toto Heriyanto (Lembaga Penelitian Universitas YARSI, 2024)
AbstractBackground: Identification in forensic medicine is done to find out someone's identity. Identification using teeth is part of the science of forensic odontology and is one of the primary identification methods. One of identification type that can be done on the teeth is using age estimation. Age estimation using third molars can be done using Harris and Nortje, and Modified-Demirjian. Autopsies are permissible for law enforcement and medical and dental sciences development. Objective: To find out the differences in the results of the estimation of dental age and chronological age using the Modified-Demirjian method and Harris and Nortje. Research Methods: This type of research is an analytic observational study with a crosssectional design. The sample for this study was 25 patients who had taken radiographic photographs at RSGM YARSI, Central Jakarta. The study used a single-blind method where one of the researchers and research respondents did not know the sample radiograph which would be analyzed. Results: there was no significant difference between chronological age and dental age using the Harris and Nortje method (p=0.58). There was no significant difference between chronological age and dental age using the Modified-Demirjian method (p=0.65). Conclusion:estimating age using teeth requires more than 1 method, especially if uses third molars Keywords: Chorological age, dental age, modified-Demirjian method, Harris and Nortje method